Synthesis of carboxy‐polyethylene glycol‐amine (CA (PEG)n) and [1‐14C]‐CA (PEG)n via oxa‐Michael addition of amino‐polyethylene glycols to propiolates vs to acrylates. (13th December 2019) - Song, Fengbin; Chen, Lu; Lin, Ronghui; Salter, Rhys
Abstract: Synthesis of carboxy‐polyethylene glycol‐amine (CA (PEG)n ) via oxa‐Michael addition of amino‐polyethylene glycols to either acrylates or propiolates was investigated. Compared with the oxa‐Michael addition to acrylates, the corresponding addition to propiolates was found to proceed under mild reaction conditions and afford the adducts in high yields from a broad scope of substrates. A two‐step efficient and convenient synthesis of benzyl [1‐ 14 C]‐propiolate from 14 CO2 was therefore developed and utilized as a common synthon to afford practical and high yielding access to [1‐ 14 C]‐CA (PEG)n . Abstract : Synthesis of carboxy‐polyethylene glycol‐amine (CA (PEG)n ) via oxa‐Michael addition of amino‐polyethylene glycols to either acrylates or propiolates was investigated. Compared with the oxa‐Michael addition to acrylates, the corresponding addition to propiolates was found to proceed under mild reaction conditions and afford the adducts in high yields from a broad scope of substrates. A two‐step efficient and convenient synthesis of benzyl [1‐ 14 C]‐propiolate from 14 CO2 was therefore developed and utilized as a common synthon to afford practical and high yielding access to [1‐ 14 C]‐CA (PEG)n .